2007
DOI: 10.1007/s00203-007-0304-z
|View full text |Cite
|
Sign up to set email alerts
|

Lon protease promotes survival of Escherichia coli during anaerobic glucose starvation

Abstract: In Escherichia coli, Lon is an ATP-dependent protease which degrades misfolded proteins and certain rapidly-degraded regulatory proteins. Given that oxidatively damaged proteins are generally degraded rather than repaired, we anticipated that Lon deficient cells would exhibit decreased viability during aerobic, but not anaerobic, carbon starvation. We found that the opposite actually occurs. Wild-type and Lon deficient cells survived equally well under aerobic conditions, but Lon deficient cells died more rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Then, the AThTP content gradually decreased, but this was probably due to death of the bacteria: indeed, the ability to form colonies after plating on agar plates decreased and became null after 6 days (data not shown), a test generally used to determine bacterial survival [ 6 ]. Luo et al [ 7 ] reported that after two days of glucose starvation, about 54% of BL21 cells survived aerobically, which is in agreement with the present data.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Then, the AThTP content gradually decreased, but this was probably due to death of the bacteria: indeed, the ability to form colonies after plating on agar plates decreased and became null after 6 days (data not shown), a test generally used to determine bacterial survival [ 6 ]. Luo et al [ 7 ] reported that after two days of glucose starvation, about 54% of BL21 cells survived aerobically, which is in agreement with the present data.…”
Section: Resultssupporting
confidence: 93%
“…During amino acid starvation, E. coli cells accumulate inorganic polyphosphate (poly-P) that activate Lon and redirect their activity towards free ribosomal proteins [ 16 ]. Whilst the survival rate of wild-type and Lon-deficient E. coli is the same under aerobic conditions, Lon-deficient cells are more sensitive to anaerobic conditions [ 7 ]. The degradation of these proteins releases amino acids that can be used to make enzymes required for amino acid metabolism [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Streptomycin-treated mouse is a model of choice for studying intestinal colonization of EHEC strains ( Luo et al, 2008 ) and has been extensively used for this purpose ( Leatham et al, 2009 ). The number of persistent EHEC in streptomycin-treated mouse feces is a representation of their number in the large intestine ( Leatham et al, 2009 ); where intestinal colonization is reduced, the level of EHEC in the feces is proportionately reduced ( Leatham et al, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Streptomycin sulfate was administrated to mice in their drinking water (5 g/liter) over the entire course of these experiments; this selectively removes facultative anaerobic and some strictly anaerobic bacteria ( Hentges et al, 1984 ). However, the overall population of anaerobes in mouse feces following streptomycin treatment remain unchanged ( Luo et al, 2008 ). We used fecal EHEC excretion to measure the relative intestinal colonizing abilities of EHEC O157:H7 strain EDL933 and EHEC O26:H11 strain 21765.…”
Section: Methodsmentioning
confidence: 99%
“…A set of proteins involved in arginine, glutamate, lysine and citrate biosynthesis (ArgABCGI, GdhA, LysC, GltA) and periplasmic proteins arginine high-affinity import (ArtJ), histidine high-affinity import (HisJ), molybdate import (ModA), and lysozyme inhibition (PliG) decreased dramatically in SynH2 cells relative to SynH2 − cells without corresponding reductions of their transcripts. GdhA, other biosynthetic enzymes, and other periplasmic binding proteins are degraded by the ClpP protease during C or N starvation (Maurizi and Rasulova, 2002 ; Weichart et al, 2003 ); Lon protease also has been implicated in proteolysis upon C starvation (Luo et al, 2008 ). Thus, we suggest that aromatic inhibitors may enhance degradation of proteins involved in N and C metabolism in stationary phase cells.…”
Section: Resultsmentioning
confidence: 99%